(untitled) (Journal of the College of Basic Education, 2022)
The era in which we live is characterized by the speed of development and change, as the knowledge explosion is one of the most important features of development in our present era, which led to the great development that occurred in the methods of education and education to keep pace with the cultural and technological progress. Perhaps art education is a basic and important pillar in education, as it seeks to provide students with experiences and performance skills, which is one of the most prominent fields of education. Plastic arts (drawing, sculpture, pottery, design, calligraphy of all kinds) occupied an important part in the art education curriculum, because of its role Active and essential in conveying ideas and leaving an impact on the recipient on cultural references, skills and creativity. Its techniques, which differ from era to era, and which have undergone many developments. In this research, the researcher referred to the Arabic (Kufic) calligraphy.